Translation and the growth of juristic discourse in sixteenth-century Ottoman political writing - Erbil, Arif. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The sixteenth century was a scene of great political, social, intellectual, religious, bureaucratic, and military novelties and transformations in Eurasia. The Ottoman Empire was no exception. On the contrary, Ottomans experienced radical shifts in most of the above-stated fields, such as advancements in record-keeping practices and, perhaps most importantly, an increasing emphasis on law after ambitious claims to universal dominion based on mystical expectations had subsided. It ought to be expected that the style and language of Ottoman political thought also responded to such changes by adjusting its tone and developing new discourses, as can be observed in the proliferation of juristic discourse in Ottoman political literature. The present thesis contextualizes the primary sources that can be considered representative of Ottoman juristic political thought and addresses the question of how and why such language spread throughout the sixteenth century. To understand this phenomenon, it examines sources or genres in which such an emphasis can be observed; looks for the broader religious, political, and intellectual contexts of the period; and also focuses on the cultural and intellectual dimensions of the Ottoman Arab encounter following the Ottoman conquests in 1516-1517, with a particular interest on three Ottoman translations of two Mamluk politico-juridical treatises: Najm al-Dīn al-Tarsūsī’s (d. 1357) Tuhfat al-Turk and al-Khayrabaytī’s (d. 1504) al Durra al-Garrā.
Keywords: Canon law -- Turkey.